Convergence of Mortality Rates among Patients on Antiretroviral Therapy in South Africa and North America - Binagwaho, Agnes (Public Library of Science, 2014)
Agnes Binagwaho and colleagues explore the narrowing gap between South African and North American cohorts in survival on HIV treatment, described in the study by Andrew Boulle and colleagues. Please see later in the article for the Editors' Summary